Telaah Product Quality, Brand Image, dan Brand Trust dalam Membentuk Customer Satisfaction dan Brand Switching Konsumen BBM Non-Subsidi dari Pertamina ke SPBU Swasta di DKI Jakarta - Dzaid Harris Putra Fahyat; Usep Suhud; Daru Putri Kusumaningtyas (Indo Publishing, 2026)
This study aims to analyze the influence of product quality, brand image, and brand trust on customer satisfaction and brand switching among non-subsidized fuel consumers switching from Pertamina to private gas stations in DKI Jakarta. The research employs a quantitative associative-causal design with a cross-sectional time horizon. Data were collected through questionnaires distributed to 210 respondents selected via purposive sampling, comprising consumers residing in DKI Jakarta, aged at least 17 years, owning a private motor vehicle, and having used non-subsidized fuel from both Pertamina and private gas stations. Data were analyzed using covariance-based Structural Equation Modeling (SEM) with AMOS, preceded by validity and reliability tests using SPSS. The results show that product quality, brand image, and brand trust have no significant direct effect on brand switching, and that product quality and brand image likewise have no significant effect on customer satisfaction. Brand trust, however, has a positive and significant effect on customer satisfaction, which in turn has a positive and significant effect on brand switching. These findings suggest that customer satisfaction serves as the key mediating factor linking brand trust to brand switching, since the direct effects of the three independent variables on brand switching were not significant, while the indirect path through customer satisfaction proved significant. This study is expected to contribute theoretically to consumer behavior research in the energy sector, and practically to PT Pertamina, private gas station operators, and the government in formulating strategies to enhance satisfaction and loyalty among non-subsidized fuel consumers.